2013
DOI: 10.1142/s0218301313300129
|View full text |Cite
|
Sign up to set email alerts
|

Short Distance Repulsion Among Baryons

Abstract: We review recent investigations on the short distance behaviors of potentials among baryons, which are formulated through the Nambu-Bethe-Salpeter (NBS) wave function. After explaining the method to define the potentials, we analyze the short distance behavior of the NBS wave functions and the corresponding potentials by combining the OPE (operator product expansion) and a renormalization group analysis in the perturbation theory of QCD. These analytic results are compared with numerical results obtained in la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We suspect that this non-smooth and scattered structure is related to a singular behavior of the NBS wave function at short distances, caused by quark creation/annihilation processes in this channel. According to the argument by the operator product expansion [49][50][51][52][53], the I = 1 ππ operator at the sink strongly couples to the ρ operator at short distance, whose mass dimension is lower than the ππ operator by 3, and the NBS wave function behaves as ψ W (r) ∼ 1 r 3 Y l=1,m=0 (Ω r ) at short distances. This implies that the NBS wave function is highly localized and singular around the origin, which is indeed the case in the point-sink scheme, as seen in Fig.…”
Section: Nrmentioning
confidence: 99%
“…We suspect that this non-smooth and scattered structure is related to a singular behavior of the NBS wave function at short distances, caused by quark creation/annihilation processes in this channel. According to the argument by the operator product expansion [49][50][51][52][53], the I = 1 ππ operator at the sink strongly couples to the ρ operator at short distance, whose mass dimension is lower than the ππ operator by 3, and the NBS wave function behaves as ψ W (r) ∼ 1 r 3 Y l=1,m=0 (Ω r ) at short distances. This implies that the NBS wave function is highly localized and singular around the origin, which is indeed the case in the point-sink scheme, as seen in Fig.…”
Section: Nrmentioning
confidence: 99%
“…This amplitude is then inserted into a Schrödinger equation in order to deduce the baryon-baryon potential that would generate it. More recently, the same idea has been used to extract short-distance potentials through the operator product expansion of perturbative QCD [7][8][9][10]. A review of the approach can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a complicated structure with rapid changes of the 3-point function around the origin, the corresponding potential shows multi-valued behavior at short distances, which is, however, NOT caused by contaminations of higher partial waves due to a cubic box (long distance effects), as discussed below. Due to quark-antiquark annihilations possible in this channel, the operator-product expansion [32][33][34][35] predicts a behavior of the 3-point function at r → 0 as…”
mentioning
confidence: 99%